Resveratrol and temozolomide induce apoptosis and suppress proliferation in glioblastoma cells via the apoptotic signaling pathway - Görkem Tutal Gürsoy; Mehmet Cudi Tuncer; İlhan Özdemir (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: Glioblastoma (GBM) is the most common primary brain tumor in the central nervous system. Studies revealing the molecular mechanisms regulating GBM pathogenesis are currently limited. This study aimed to investigate the expression of genes responsible for the apoptotic pathway (p21, p27, p53) after separate and combined application of the natural components resveratrol (Res) and temozolomide (TMZ) in the GBM cell line (U118). Methods: In this study, the GBM cell line U118 was used. Apoptotic activation of Res and TMZ via the p21, p27, p53 signaling pathway was evaluated by quantitative reverse transcription polymerase chain reaction and TaLi cytometry. Cell viability was also assessed using the MTT assay. Results: Res and TMZ inhibited the proliferation and migration of U118 cells. Additionally, Res induced apoptosis by arresting the cell cycle. Moreover, Res treatment upregulated the expression of p27 and p53, which are associated with apoptosis, while it significantly downregulated the expression of the p21 gene. Conclusion: These results indicated that Res and TMZ suppressed the proliferation of GBM cells through apoptotic pathways. Together, Res and TMZ may represent a promising combination for suppressing tumors through apoptotic mechanisms.